2023
DOI: 10.3390/w15163001
|View full text |Cite
|
Sign up to set email alerts
|

Study on Water and Salt Transport under Different Subsurface Pipe Arrangement Conditions in Severe Saline–Alkali Land in Hetao Irrigation District with DRAINMOD Model

Feng Tian,
Qingfeng Miao,
Haibin Shi
et al.

Abstract: As an effective method to improve saline–alkali land, the drainage from subsurface pipes has been extensively studied in typical arid and semi-arid agricultural areas (Hetao Irrigation District). However, there are few studies on the improvement of subsurface pipe layout and the long-term soil salinization control in the process of leaching and soil amendment with subsurface pipes in this area. This study investigated the water and salt migration in the process of amending the heavy saline soil. Field experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In the study by Zou, the maximum rooting depth of maize roots at the grain filling stage was 100 cm, whereas the maximum rooting depth was limited to the depth of the sand layer in the present study. Generally, roots increase their surface area to absorb water and nutrients to meet the normal growth needs of crops [58][59][60][61]. In this study, we found that RL in the horizontal and vertical directions was significantly correlated with yield and WUE, with the highest correlation observed in NR20.…”
Section: Discussionmentioning
confidence: 51%
“…In the study by Zou, the maximum rooting depth of maize roots at the grain filling stage was 100 cm, whereas the maximum rooting depth was limited to the depth of the sand layer in the present study. Generally, roots increase their surface area to absorb water and nutrients to meet the normal growth needs of crops [58][59][60][61]. In this study, we found that RL in the horizontal and vertical directions was significantly correlated with yield and WUE, with the highest correlation observed in NR20.…”
Section: Discussionmentioning
confidence: 51%
“…The lack of isotope data with high temporal resolution along the soil-plant-atmosphere axis and the effects of isotope fractionation complicated our analysis of yellow willow water sources. To increase the accuracy of water source identification, future studies should examine the isotope fractionation mechanisms in yellow willow water sources [49], specifically the differences between various plant tissues and soil layers [50][51][52][53], and consider other models and/or data correction factors. To more precisely record short-term changes in the isotopic compositions of soil, plants, and atmospheric water, high-precision isotope analyzers should be employed with a higher sample frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Soil salinity is a major factor affecting soil fertility and crop yield [40,41], and one of the most important indicators for assessing the degree of soil salinity [42]. The measurement of soil salinity is very important for the improvement of saline soils, so through the combination of soil bulk conductivity, soil solution conductivity, and volumetric water content, the ECWS model of soil salinity has been proposed, which is very important for soil salinity monitoring.…”
Section: Discussionmentioning
confidence: 99%